Screening Life Cycle Assessment of Upscaling Structural Battery Composite Production - Balaji, Suveer (My University, 2025)
Structural batteries are composite materials which incorporate lithium-ion battery (LIB) cells to bear mechanical loads as well as receive and release electrical energy. This multi-functionality of structural batteries helps to reduce weight significantly as separate entities for structural support and energy storage are not required unlike in the case of conventional battery technologies. The structural battery is seeing growing demand in transportation systems, consumer electronics and biomedical applications. However, the structural battery technology is currently being implemented only at laboratory scale. The measures and challenges associated with physically scaling structural battery composite production are uncertain. This study focuses on evaluating environmental impacts when considering scenarios related to physically scaling the production of structural battery composites (SBC) from laboratory scale to pilot scale using screening life cycle assessment (LCA). The scenarios in relation to varying electrolyte to epoxy resin composition of SBC were built, developed and analyzed in this study. The results from modelling of scenarios showed considerable increase in climate change impacts, ecotoxicity (terrestrial) impacts, ozone depletion, ionising radiation and water use impacts when structural battery composite production was physically scaled from laboratory to pilot scale. The environmental hotspots determined from the study were the use of carbon fibers, production of certain structural electrolyte constituents, consumption of electricity in production processes as well as electrolyte infusion and curing processes. The report also explains the gaps in research and recommendations for future research in relation to scaling SBC production to minimize environmental impacts associated with these processes.
Keywords: LCA; Batteries; Engineering; Sustainability; Scenario Analysis